Karyotype studies in Mimosa (Mimosoideae, Leguminosae) from Southern South America and ecological and taxonomic relationships - Morales, Matias (2011)
In this work we studied the chromosome number and karyotype formula of seven species of Mimosa L. (Mimosoideae, Leguminosae). The chromosome number 2n = 2x = 26 for M. detinens Benth., M. hex- andra M. Micheli, M. ostenii Speg. ex Burkart and M. xanthocentra Mart. var. mansii (Benth.) Barneby are new records, while the chromosome number 2n = 2x = 26 for M. debilis var. debilis, M. urugüensis Hook. and Arn. and M. uliginosa Chodat and Hassl. confirm previous records. Karyotype formulae revealed the existence of metacentric and submetacentric chromosomes, and the chromosomal asymmetry indexes did not show significant differences between taxa. The chromosome length of xerophilous and endemic M. detinens and M. ostenii differed from the rest of species, indicating that this parameter could have taxonomic value. In addition, the relationship between total chromosome length and climatic parameters showed that diploid species of marginal areas of distribution have a larger chromosome size, and that this could be related with mechanisms of ecologi- cal adaptation.